CHINA AND VIETNAM IN THE SOUTH CHINA SEA: DISPUTES AND STRATEGIC QUESTIONS - Pinotti, Talita (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The dispute between China and Vietnam in the South China Sea involves strategic interests that are mixed with cultural and historical heritages fundamental to the understanding of their respective positions. Ensure the sovereignty over the islands, for these countries, also means to ensure important economic and geopolitical interests in Asia.